Productivity and nitrogen-use efficiency yardsticks in conventional and Bt cotton hybrids on rainfed Vertisols - Venugopalan, M V; Deshmukh, Rachana; Hebbar, K B; Tandulkar, N R (The Indian Journal of Agricultural Sciences, 2012)
The yield of Bt hybrids (MCEH 184 and RCH 2) was higher than non-Bt NCS 145 and among Bt hybrids, the medium duration RCH 32 Bt was superior to short-duration MECH 184 under normal sowing date. Under late sown conditions, the performance of both RCH 2 Bt and NCS-145 were similar and Bt hybrids are not likely to be more advantageous late sown conditions where a decline in temperature induces cut out. N UtiE and not N Upt E was primarily responsible for a higher NUE in Bt hybrids RCH 2 and MECH 184 than the non-Bt hybrid NCS-145. A higher HI enabled Bt hybrids to utilize N more efficiently.